Application of Chitosan as Cyanide Adsorbance on Gold Ore Processing - Dian Harjuna Sukma; Etty Riani; Edward Nixon Pakpahan (Jurnal Pengolahan Hasil Perikanan Indonesia, 2018)
Gold ore processing method have an impact on water pollution if the waste produced is not managed properly. Chitosan have the ability as an adsorbent, but its effectiveness to absorb cyanide content in gold processing wastewater is unknown. This study aimed to examine the ability of chitosan adsorption on cyanide in the processing of gold ore. The statistic design used was a factorial in-time Completely Randomized Design (CRD) with two repetitions. The analysis carried out consisted of the effect of chitosan concentration on absorbance, pH, TDS, turbidity, cyanide, and the modification effect of chitosan production on absorbance power. The method used in this research was flocculation coagulation method by the jar test.The method was carried out by rapid and slow mixing process with a flocullator. The method was used to determine the best of chitosan type and the best contact time to decrease the concentration of cyanide waste from the processing of gold ore. The results showed that the best concentration of chitosan modified was chitosan modification with swelling crosslink glutaraldehid (GA) in 1000 ppm concentration and using slow mixing contact time for 120 minutes. That chitosan modified significantly adsorp cyanide waste in 90.38%.